New Methods in Exploring Old Topics: Case Studying Brittle Diabetes in the Family Context. (8th November 2015) - Günther, Moritz Philipp; Winker, Peter; Wudy, Stefan A.; Brosig, Burkhard
Abstract : Background . In questing for a more refined quantitative research approach, we revisited vector autoregressive (VAR) modeling for the analysis of time series data in the context of the so far poorly explored concept of family dynamics surrounding instable diabetes type 1 (or brittle diabetes). Method . We adopted a new approach to VAR analysis from econometrics referred to as the optimized multivariate lag selection process and applied it to a set of raw data previously analyzed through standard approaches. Results . We illustrated recurring psychosomatic circles of cause and effect relationships between emotional and somatic parameters surrounding glycemic control of the child's diabetes and the affective states of all family members. Conclusion . The optimized multivariate lag selection process allowed for more specific, dynamic, and statistically reliable results (increasing R 2 tenfold in explaining glycemic variability), which were derived from a larger window of past explanatory variables (lags). Such highly quantitative versus historic more qualitative approaches to case study analysis of psychosomatics surrounding diabetes in adolescents were reflected critically.